Impact of vaccination on keratoplasty. Issue 4 (July 2022) - Dugan, Sarah P.; Mian, Shahzad I.
Abstract : Purpose of review: Corneal graft rejection has been reported after coronavirus disease 2019 (COVID-19) vaccination. The purpose of this review is to evaluate the literature regarding corneal graft rejection after vaccination, including rejection rates and risk factors. We aim to create a framework to identify patients who are at higher risk for graft rejection and may warrant consideration of prophylactic interventions. Recent findings: Graft rejection has been reported following administration of mRNA, viral vector, and inactivated whole-virion COVID-19 vaccines. Most cases had additional risk factors associated with rejection. Vaccination increases circulation of proinflammatory cytokines, CD4+ and CD8+ T-cell responses, and antispike neutralizing antibody, all of which may contribute to graft rejection. Two prospective studies have found no relationship between recent vaccination and rejection but 20% of cornea specialists report to have seen a vaccine-associated rejection and 22% recommend delaying vaccination in certain circumstances. Many specialists recommend prophylactic topical corticosteroids before and after vaccination to mitigate rejection risk but there is no evidence to support this practice on a wider scale. Summary: Our framework identified 96.8% of penetrating keratoplasty patients with vaccine-associated rejection as higher risk. Further research is needed in order to develop evidence-based guidelines.